Improving Record Efficiency: An Analysis of Inactive Record Management at the Center for Drug and Food Control in Bandar Lampung, Indonesia - Parangu, Reza Nawafella Alya; Meilani, Feni; Setiawan, Agus Mahfudin; Kanzulfikar, Achmad (Ilmu Informasi Perpustakaan dan Kearsipan, 2025)
Document control is a crucial aspect of office work related to the management of records. Given the vital role records play in providing accurate, timely, relevant, and complete information, records management must be optimized to support decision-making and policy formulation by leaders. Well-managed office records are easier to retrieve when needed. This study aims to examine the management of inactive records as well as the inhibiting and supporting factors at BBPOM Bandar Lampung. The research employed a descriptive method with a qualitative approach, using data collection techniques such as observation, interviews, literature review, and documentation. Data analysis included reduction, presentation, and verification, while data validity was tested through source and technique triangulation. The findings indicate that the management of inactive records at BBPOM generally aligns with established mechanisms, as BBPOM has implemented a Records Retention Schedule (RRS) for the storage and disposal of records. However, there are several challenges in record management, such as limited storage space and large volumes of records, which have resulted in many records being improperly organized. Additionally, data from 2018-2021 show that the lack of human resources (HR) in archiving and limited facilities also hinder the management of inactive dynamic records, causing delays in task completion within the set deadlines. According to ANRI regulations, HR is a key factor in records management. Nevertheless, there are also supporting factors for managing inactive dynamic records at BBPOM, such as scheduled record destruction, the existence of a comprehensive archiving SOP, and a proposal to increase HR in archiving by 2025